A CUDA-Based Implementation of a Fluid-Solid Interaction Solver: The Immersed Boundary Lattice-Boltzmann Lattice-Spring Method (Communications in Computational Physics, 2020)
The immersed boundary lattice-Boltzmann lattice-spring method (IBLLM)has previously been implemented to solve several systems involving deformable andmoving solid bodies suspended in Navier-Stokes fluids, but these studies have generallybeen limited in scope by a lack of computing power. In this study a GraphicsProcessing Unit (GPU) in CUDA Fortran is implemented to solve a variety of systems,including a flexible beam, stretching of a red blood cell (RBC), and an ellipsoid undershear flow. A series of simulations is run to validate implementation of the IBLLM andanalyze computing performance. Results demonstrate that an Intel Xeon E5645 fittedwith an NVIDIA Tesla K40 graphics card running on a GPU improves computationalspeed by a maximum of over 80-fold increase in speed when compared with the sameprocessor running on a CPU for solving a system of moderately sized solid and fluidparticles. These studies represent the first report on using a single GPU device withCUDA Fortran in the implementation of the IBLLM solver. Incorporation of a GPUwhile solving with the versatile IBLLM technique will expand the range of complexfluid-solid interaction (FSI) problems that can be solved in a variety of fields.